Surface strengthening and repairing material for hydraulic concrete, and application thereof - LIU ZHIJIE; WANG WENJIAN; ZHAO LIN; YANG GUIXIN; WU JIN (2017)
The invention discloses a surface strengthening and repairing material for hydraulic concrete, and application thereof, belonging to the field of hydraulic structures. The surface strengthening and repairing material is prepared by mixing raw materials consisting of acrylic emulsion, mineral powder, cement, fine sand and water. Since the mineral powder is used for equivalent replacement of cement to improve acrylic emulsion mortar, so the prepared material has the characteristics of good anti-compression performance, flexural strength, bonding strength and durability, convenience in construction, etc., and can meet different engineering needs by adjusting the addition amount of the mineral powder; and the material can be used for protection of a concrete structure, is extensively applicable as a repairing material in restoration works, and has high application value. 本发明公开了种水工混凝土表面强化修补材料及其应用，涉及水工结构领域；该强化修补材料是由丙乳、矿粉、水泥、细砂、水为原料混合而成；通过矿粉等量取代水泥的方式对丙乳砂浆的性能进行提升，具有良好的抗压、抗折、粘结强度、耐久性好以及施工方便等特点，并且可以通过调整矿粉掺量以满足不同的工程需要；本